Spatiotemporal analysis of 289 world-class 400-meter running performances - Schwarz, Y.; Wiedenmann, T.; Lemberg, P.; Böddeker, K.; Christmann, R.; Schwarz, A.; Rein, R.; Braunstein, B. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Sprint running performance is the product of the spatiotemporal variables step frequency [SF] and length [SL].[1] While the 100-m dash has been in the spotlight of biomechanical investigations, less research has looked at the 400-m distance. Hence, purpose of this study was to extract spatiotemporal parameters from a large sample of world-class 400-m performances and gain insights on potential determining factors. METHODS: Publicly available video footage was obtained from 84 world-class 400m races (Olympics, World & Europ. Champ., Diamond League), including 289 performances of 101 athletes (m=51; f=50) between 2015 to 2020. Footage was only considered valid if athletes were visible without interruption and if markings were visible every 100m. Time and step count were extracted visually and mean velocities, SL and SF calculated for each 100m section of the race. Differences in performance and sex were evaluated via Welch two sample t-test for every section. RESULTS: Over the entire 400m distance, mean velocity was 8.85±0.15 m*s-1 for male and 7.81±0.14 m*s-1 female sprinters. On average male athletes displayed a SL of 2.31±0.11 m and SF of 3.84±0.17 steps*s-1, while female athletes had a mean SL of 2.09±0.09 m and SF of 3.75±0.13 m*s-1. Greater differences between men and women were found in SL (11.8%; p